If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Px + Q = -19x + 18 Reorder the terms: Q + xP = -19x + 18 Reorder the terms: Q + xP = 18 + -19x Solving Q + xP = 18 + -19x Solving for variable 'Q'. Move all terms containing Q to the left, all other terms to the right. Add '-1xP' to each side of the equation. Q + xP + -1xP = 18 + -19x + -1xP Combine like terms: xP + -1xP = 0 Q + 0 = 18 + -19x + -1xP Q = 18 + -19x + -1xP Simplifying Q = 18 + -19x + -1xP
| 4-5x=x+6-2x-2 | | 8x^3-44x^2+48x=0 | | (2x)=(103-x) | | M=35g | | 5+3c-5= | | (2x)+(103-x)+(x)=180 | | Y=x(30-2x) | | 6x+5+53=90 | | Px+40=Qx+20 | | 6x+5+53=180 | | 4x+x=17.5 | | Pix+40=Qx+20 | | H+20=35+4h | | 2x-4+4x=39 | | (7+4i)-(8+i)=0 | | -3=1(-5)+b | | (51)+(2x+3)+(x)=180 | | 3(3n+6)=30 | | c-1/2=3 | | 4-x=3x+6-4x-2 | | 6cos(x)-x-1=0 | | -110m=-4c-6c | | 4x-4=1/2x-1/2×8 | | 14p+56= | | X=(x-30)+3+(x-18)+8 | | =7y^2-5y-2 | | ax-5=b(2x+1) | | 2x-y+12=0 | | -2=1(-5)+b | | 6(3x-11)+5=9x-10 | | 3(2x+8)=-72 | | -4a+6b-4a+2b= |